Platelet-Rich Fibrin Used in Regenerative Endodontics and Dentistry: Current Uses, Limitations, and Future Recommendations for Application - Sohaib Arshad; Fatima Tehreem; Muhammad Rehab khan; Fatima Ahmed; Anand Marya; Mohmed Isaqali Karobari (Hindawi Limited, 2021)
Regenerative endodontics has introduced numerous procedures such as pulp implantation, revascularization, and postnatal stem cell therapy. Revascularization has been successfully implemented clinically nowadays, thus providing dentists with outrageous results. Platelet-rich fibrin (PRF) used either alone or along with bone graft promotes bone growth and vascularization. This matrix promotes migration, cell attachment, and proliferation of osteoblast that leads to bone formation. PRF consists of a packed fibrin complex consisting of leukocytes, cytokines, and glycoproteins such as thrombospondin. The usage of PRF has reported high success rates in surgical cases such as sinus lift procedures, healing of extraction sockets, and management of periapical abscesses. Compared to platelet-rich plasma, PRF is more economical, easy to prepare, and feasible to use in daily clinical practices. Revascularization compromised the induction of a blood clot into the root canal space, which emerged as a clinical triumph. This further led to platelet concentrates as an autologous scaffold on which revascularization could occur. The applications of PRF in regenerative endodontics are numerous, such as an agent for repairing iatrogenic perforation of the pulpal floor and for the revascularization of immature permanent teeth with necrotic pulps. It acts as a matrix for tissue ingrowth. Evidence of progressive thickening of dentinal walls, root lengthening, regression in the periapical lesion, and apical closure was reported. Further studies are needed to clarify the precise mechanism of action of PRF for dental pulp regeneration both in vitro and in vivo. The current review aims at the present uses of PRF in regenerative endodontics dentistry and its application with future recommendations and limitations.